Association between plasma trans fatty acid levels and rheumatoid arthritis: a cross-sectional study using NHANES 1999–2000 and 2009–2010 data in US adults - Li, Tanjian; Jiang, Na; Liang, Xin; Li, Xinya; Li, Yaqin; Huang, Yuting; Wang, Yu (Frontiers in Nutrition, 2024)
Objective While earlier research has indicated that trans fatty acids (TFAs) are detrimental to cardiovascular health as well as other conditions, the purpose of this study is to look into any possible connections between trans fatty acids and rheumatoid arthritis (RA). Methods 4The NHANES database provided the data for this study, covering two periods: 1999-2000 and 2009-2010. The correlation between plasma TFAs (linolelaidic acid, vaccenic acid, palmitelaidic acid, elaidic acid) and RA was examined using weighted univariate and multivariate regression analyses as well as analysis of subgroups. Additionally, this study employs restricted cubic spline curves to investigate the nonlinear relationship between them. Result This study included 2938 patients, of whom 222 (7.56%) had RA. Multivariate logistic regression analysis showed that levels of linolelaidic acid were linked to a higher risk of RA (odds ratio=1.39, 95% confidence interval=1.05-1.85, P=0.025) after accounting for all other variables. No significant effect on this association was found in interaction tests. Linolelaidic acid and RA were demonstrated to have a linear association in the limited cubic spline regression model. For RA, linolelaidic acid exhibits a critical value of 0.98. Conclusion Findings that point to a possible link between elevated plasma TFAs levels and an increased risk of RA offer fresh perspectives on RA prevention through dietary interventions.